2011
DOI: 10.1111/j.1462-2920.2011.02611.x
|View full text |Cite
|
Sign up to set email alerts
|

Methanogenesis facilitated by electric syntrophy via (semi)conductive iron‐oxide minerals

Abstract: Methanogenesis is an essential part of the global carbon cycle and a key bioprocess for sustainable energy. Methanogenesis from organic matter is accomplished by syntrophic interactions among different species of microbes, in which interspecies electron transfer (IET) via diffusive carriers (e.g. hydrogen and formate) is known to be the bottleneck step. We report herein that the supplementation of soil microbes with (semi)conductive iron-oxide minerals creates unique interspecies interactions and facilitates m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
385
6
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 550 publications
(427 citation statements)
references
References 59 publications
18
385
6
3
Order By: Relevance
“…Syntrophic interaction between Geobacter and Methanosarcina through DIET might be conducted with conductive pilis or minerals [19,32]. The poor presence of Methanobacterium and the rich presence of Methanosarcina in methanogenesis-facilitated cultures (0.5-and 5-mM AQDS-supplemented cultures) were in good agreement with the distribution of methanogenic community involved in DI-ET from Geobacter to Methanosarcina through (semi)conductive iron oxides [19].…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Syntrophic interaction between Geobacter and Methanosarcina through DIET might be conducted with conductive pilis or minerals [19,32]. The poor presence of Methanobacterium and the rich presence of Methanosarcina in methanogenesis-facilitated cultures (0.5-and 5-mM AQDS-supplemented cultures) were in good agreement with the distribution of methanogenic community involved in DI-ET from Geobacter to Methanosarcina through (semi)conductive iron oxides [19].…”
Section: Discussionmentioning
confidence: 55%
“…The genus Geobacter has been surprisingly discovered to be capable of forming highly conductive network of pilis that facilitate long-range electron transfer [34,38,39], which is becoming an important feature of Geobacter species in anaerobic environments [17,26,27]. There is increasing evidence that Geobacter species are important syntrophic microorganisms capable of establishing syntrophic association with methanogens [19,29,45]. Recent study demonstrated the possibility of direct interspecies electron transfer (DIET) between Geobacter species and Methanosaeta concilii within upflow anaerobic sludge blanket reactor methanogenic aggregates, which were electrically conductive largely contributed by Geobacter species [32].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations